(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-219-229 The relevance of the study is considered to the current situation of difficult relations between Russia and Europe. The aim of the research is to study the specifics of the European personalities representation in the magazine “Sovremennik” in 1848 as a period of time when the audience’s attention was focused on censorship and reflected all the events abroad in the press. The main research methods are content-analysis and classification, which allow to solve the following aims: to identify the representation of Europeans in different magazine sections, using different genre forms, to determine the types of publications heroes depending on their field of activity and gender. The analysis showed that “Sovremennik”, in the year of a rapid change in the state course in connection with the revolutionary events called the “Spring of Nations”, maintained a cross-cultural orientation and created an image of a diversity in Europe through mentioning vivid persons among scientists, representatives of literature and art, statesmen, church ministers of different eras and countries into texts of different genres (from notes to essays), travelers. Key words: history of Russian journalism of the 19th century, “Sovremennik” magazine, Europeans, literary criticism, theater criticism, essay